The plight of China’s journalism education - From the perspective of the sociology of education - Hao, Li (Technium Social Sciences Journal, 2021)
China’s journalism education has been changing all the time to meet new demands brought by the political and economic reforms over the last two decades in the 21st century. However, the covert wars between ideology and practice, between classrooms and newsrooms have caused the “split personality” and general confusion among China’s journalism educators and students. Several educational and practical problems thus arise as a result of the tug-of-war between economic and ideological demands. The problems of China’s journalism education are not only from its complex social and economic environments, but also from its weight of history and culture. Although both journalism educators and some media organizations in China are making great effort to heighten awareness of problems and actively attempting to take remedial measures, the transition from the classroom to the newsroom is made more difficult by the complicatedness of the business operation of schools and media organizations, and the systematicity of journalism education remains problematic.